THE MUNICIPAL DEBT COLLECTION BEYOND THE MATHABATHE CASE – A WELCOME SOLUTION OR MULTIPLICATION OF PROBLEMS? City of Tshwane Metropolitan Municipality v Mathabathe (502/120) [2013] ZASCA 60 - Matome M Ratiba (Obiter, 2014)
South Africa prides itself as a country with the best land-registration system in the world. However, the intoxicating affect of such a rosy picture as depicted in the legal literature and pertaining to the land registration system in this country continues to hold and tantalise the mind of a novice property practitioner until, at least one arrives at the point where the actual processes involved in effecting the transfer of property and the eventual registration of a title deed to the property are engaged. This is the exact point where one begins to experience the lived realities of the frustrations often meted out to the relevant process participants such as the transferring attorneys, sellers and purchasers of property alike and least of all not forgetting the financial institutions. The turning point starts with section 92 of the Deeds Registries Act 47 of 1937 (hereinafter “the Deeds Act”) in terms of which no transfer of land may (shall) be registered without a rates-clearance certificate from the local authority in whose jurisdiction the land lies. The comedy of errors often accompanying the efforts geared towards practical compliance with the section leaves much to be desired. It is in the context of such problems arising during the processes of obtaining rates-clearance certificates from the municipality that the need to critically evaluate the recent supreme court of appeal judgment in the case of City of Tshwane Metropolitan Municipality v Mathabathe ((502/12) [2013] ZASCA 60 emanates. Such a need is further bolstered by the fact that, practical problems that were experienced in the case under discussion should be acknowledged, and always be kept in mind when judgements similar to the one under discussion are analysed. The reality of it all is that “In South Africa, the management of municipal services has been an ongoing dilemma for the new government because of what it terms ‘a culture’ of non-payment among users”. The purpose of this note is therefore to critically evaluate the Mathabathe case with a view to determining whether the judgment in the case constitutes a welcomed solution to a long-standing problem or not. This will be done in three parts. In the first part an outline of the contextual background within which the evaluation is to take place will be presented. This entails detailing the dilemma often facing the municipalities in the provision of services and the legal framework pertaining thereto, coupled with a brief description of how the same translates into frustrations often directed at various participants in the receiving end of the property-registration process. The second part will provide a brief outline of the facts and decision of the Mathabathe case. The last part will give an analysis of the relevant decision, which analysis will also discuss the important issues raised by the practical implementation of the judgment.